Body mass index associates with amyotrophic lateral sclerosis survival and metabolomic profiles. Issue 3 (18th November 2022) - Goutman, Stephen A.; Boss, Jonathan; Iyer, Gayatri; Habra, Hani; Savelieff, Masha G.; Karnovsky, Alla; Mukherjee, Bhramar; Feldman, Eva L.
Abstract: Introduction/Aims: Body mass index (BMI) is linked to amyotrophic lateral sclerosis (ALS) risk and prognosis, but additional research is needed. The aim of this study was to identify whether and when historical changes in BMI occurred in ALS participants, how these longer term trajectories associated with survival, and whether metabolomic profiles provided insight into potential mechanisms. Methods: ALS and control participants self‐reported body height and weight 10 (reference) and 5 years earlier, and at study entry (diagnosis for ALS participants). Generalized estimating equations evaluated differences in BMI trajectories between cases and controls. ALS survival was evaluated by BMI trajectory group using accelerated failure time models. BMI trajectories and survival associations were explored using published metabolomic profiling and correlation networks. Results: Ten‐year BMI trends differed between ALS and controls, with BMI loss in the 5 years before diagnosis despite BMI gains 10 to 5 years beforehand in both groups. An overall 10‐year drop in BMI associated with a 27.1% decrease in ALS survival ( P  = .010). Metabolomic networks in ALS participants showed dysregulation in sphingomyelin, bile acid, and plasmalogen subpathways. Discussion: ALS participants lost weight in the 5‐year period before enrollment. BMI trajectories had three distinct groups and the group with significant weight loss in the past 10 years had the worst survival. Participants with a high BMI and increase in weight in the 10 years before symptom onset also had shorter survival. Certain metabolomics profiles were associated with the BMI trajectories. Replicating these findings in prospective cohorts is warranted. Abstract : See Editorial on pages 191‐192 in this issue